Pengembangan Sistem Pengelolaan Praktikum berbasis Web (Studi Kasus: Fakultas Ilmu Komputer Universitas Brawijaya) - Asa Kartika Indrajati; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Faculty of Computer Science Universitas Brawijaya organizes education in the form of seminars, field work, lecture activities, practical work, field work, and structured and independent academic activities. Practicum is an academic activity that can be carried out in a laboratory or in other places that have been determined. At present, the implementation of practicum in the Faculty of Computer Science, Universitas Brawijaya has a problem such as the absence of self-organized resources to access matters related to practicum activity, causing important information to be missed such as opening new recruitment lab assistants. Then, the late collection of selection needs because of less efficient communication led to the late opening of a lab assistant recruitment. So for a solution, a web-based Practicum Management System was developed which is expected to help coordinate the preparation and implementation of coordination. Web development using the CodeIgniter Framework with PHP technology. Approval in developing this web using object-oriented documentation is approved using the Unified Modeling Language (UML). While the development cycle is done by the Waterfall method. For the testing process using unit, integration, validation, and compatibility testing. The results of testing with black-box and white-box techniques show 100% valid results. While from compatibility testing there were no issues.